2022
DOI: 10.3389/frph.2021.780931
|View full text |Cite
|
Sign up to set email alerts
|

Postmenopausal Vaginal Microbiome and Microbiota

Abstract: The ovulatory cycle has a significant influence on the microbial composition, according to the action of estrogen and progesterone on the stratified squamous epithelium, due to an increase in epithelial thickness, glycogen deposition, and influence on local immunology. The 16S rRNA gene amplification and pyrosequencing study demonstrated that healthy women have community state types (CST), classified as; type “L,” with a predominance of Lactobacillus crispatus, type II, with a predominance of Lactobacillus gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…Humans are host organisms with stable and transient symbiotic microbiota [ 1 ]. A balanced interaction between the host and microbiota is crucial to maintaining host health [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Humans are host organisms with stable and transient symbiotic microbiota [ 1 ]. A balanced interaction between the host and microbiota is crucial to maintaining host health [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Menopause is the conclusion of the menstrual cycle in relation to ovarian failure due to reduced estrogen secretion and the loss of progesterone secretion, and with increased life expectancy, the postmenopausal period may account for up to one-third of a woman’s life [ 1 ]. The dramatic changes in a woman’s health after menopause are well-known, and menopause alters the gut microbiota, which has several effects on a woman’s health [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because significant differences were seen in successful initial colonization and duration of colonization between mice within the same treatment group, we considered other factors that could affect the colonization. The transition of women through menopause is marked by a gradual depletion of Lactobacillus species and an increase in anaerobic bacteria (Oliveira et al, 2022). Others have reported that mice given 17β-estradiol are more likely to be colonized by BV associated bacteria (Gilbert et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…90 Low oxygen levels prevalent in reproductive tissues foster stem cell maintenance, while anaerobic or microaerophilic conditions favor the growth of specific reproductive tract microbes. 91 Conversely, changes in local oxygen levels during inflammation and disease may dramatically alter host-microbe dynamics. 92 However, replicating these conditions within organoid models is complex, as the standard oxygen concentration in organoid cultures (around 20%) contrasts sharply with the in vivo reality of less than 5% oxygen.…”
Section: Modeling Oxygen Levelsmentioning
confidence: 99%